Energetics of Technical Integration of 2-Propanol Fuel Cells: Thermodynamic and Current and Future Technical Feasibility - Braun, Katharina; Wolf, Moritz; de Oliveira, Ana; Preuster, Patrick; Wasserscheid, Peter; Thiele, Simon; Weiß, Lukas; Wensing, Michael (Energy Technology, 2022)
2-Propanol/acetone is a promising liquid organic hydrogen carrier system for fuel cell reactions. Herein, six different concepts for a 2-propanol/acetone fuel cell system are evaluated in MATLAB simulation with respect to their thermodynamic integration and technical feasibility. Four of the concepts use a direct 2-propanol fuel cell while the other two first release molecular hydrogen from 2-propanol and subsequently use a hydrogen fuel cell. The presented liquid phase 2-propanol fuel cell concept is thermodynamically feasible but cannot be realized technically using commercial Nafion membranes, due to membrane dissolution by the 2-propanol/acetone/water fuel mixture. Gaseous 2-propanol fuel cells imply a high heating requirement for the evaporation of the fuel. A direct high-temperature fuel cell using 2-propanol is thermodynamically feasible because there is less water in the overall system but is not technically feasible because of the esterification of phosphoric acid. A very interesting option is the conversion of gaseous 2-propanol to pressurized hydrogen in an electrochemical pumping step followed by a hydrogen fuel cell, because here the waste heat of a sufficiently hot hydrogen fuel cell can drive the 2-propanol evaporation.
CRIS-Team Scopus Importer:2022-07-15
Keywords: 2-propanol fuel cell system; balance of plant; energy balancing; system integration; technical integration